Dynamic findings of brain magnetic resonance imaging in a haploidentical hematopoietic stem cell transplantation recipient with cytomegalovirus ventriculoencephalitis: a case report and systematic review - Li, Nannan; Zhao, Jing; Liu, Yinghui; Zhang, Yuanfeng (Frontiers in Immunology, 2024)
Our case demonstrated unique cytomegalovirus (CMV) encephalitis post-haploidentical donor hematopoietic stem cell transplantation (HID-HSCT), with early findings on diffusion-weighted brain magnetic resonance imaging (MRI) in the absence of any neurologic symptoms. A 54-year-old Chinese man with acute lymphoblastic leukemia (Philadelphia chromosome-negative) underwent HID-HSCT.After HSCT, the patient developed CMV viremia and severe acute graft-versus-host disease. Recurrence of CMV viremia was observed. On day 129, brain MRI was performed to determine the cause for the intermittent fever. Diffusion-weighted imaging (DWI) revealed several bright spots in the cortex of the frontal lobes and anterior angle of the left lateral ventricle. Subsequently, he developed transplant-associated thrombotic microangiopathy, posterior reversible encephalopathy syndrome, and enlargement of lesions alongside the ventricular wall on a brain MRI series. Metagenomic next-generation sequencing (NGS) of the cerebrospinal fluid (CSF) led to the final diagnosis of CMV encephalitis. Although ganciclovir combined with foscarnet was administered, the patient's consciousness deteriorated, followed by respiratory failure. The patient died on day 198. Additionally, we performed a systematic review to comprehensively analyze this disease. Regarding treatment, immunological therapies, including virus-specific T cells from a third donor and CMV-cytotoxic T lymphocytes, may be more effective. This case report and systematic review underscores the complexities of managing CMV ventriculoencephalitis in HSCT recipients and emphasizes the importance of early diagnosis by brain MRI and CSF polymerase chain reaction or NGS and ongoing research in improving outcomes.